2014
DOI: 10.1161/circresaha.114.301597
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Lipidomics

Abstract: Lipids are diverse families of biomolecules that perform essential structural and signaling roles in platelets. Their formation and metabolism is tightly controlled by enzymes and signal transduction pathways, and their dysregulation leads to significant defects in platelet function and disease. Platelet activation is associated with significant changes to membrane lipids, and formation of diverse bioactive lipids that play essential roles in hemostasis. In recent years, new generation mass spectrometry analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(59 citation statements)
references
References 168 publications
5
54
0
Order By: Relevance
“…We conducted incubations under stirring conditions because this better predicts platelet reactivity in the body than static conditions (17). As others and we have reported previously (9, 18, 19), activated platelets produce a broad range of AA-derived eicosanoids. Notably, in our studies we found 11-HETE and 15-HETE to be major products formed at similar levels to TXA 2 through the action of group IV A cytosolic phospholipase A 2 and COX-1.…”
Section: Discussionsupporting
confidence: 82%
“…We conducted incubations under stirring conditions because this better predicts platelet reactivity in the body than static conditions (17). As others and we have reported previously (9, 18, 19), activated platelets produce a broad range of AA-derived eicosanoids. Notably, in our studies we found 11-HETE and 15-HETE to be major products formed at similar levels to TXA 2 through the action of group IV A cytosolic phospholipase A 2 and COX-1.…”
Section: Discussionsupporting
confidence: 82%
“…Therapeutic reduction of cardiovascular disease progression and events has focused on limiting platelet activation through inhibition of cyclooxygenase (COX), phosphodiesterase, adenosine diphosphate (ADP) receptors, and platelet-platelet interactions through glycoprotein IIb/IIIa (Yousuf & Bhatt, 2011). Major lipid remodelling occurs upon platelet activation that includes shape change, degranulation and generation of a number of bioactive species that amplify activation while promoting clot stabilization and inflammation (O’Donnell, Murphy, & Watson, 2014). Oxylipins are a superclass of bioactive lipids produced from polyunsaturated fatty acid oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in analytical technology and instrumentation have enabled more robust and sensitive methods for detection and identification of these small molecules, leading to a greater understanding of their involvement in disease pathology(Schmelzer et al 2007, Loizides-Mangold 2013, O’Donnell et al 2014). First coined a little over a decade ago, lipidomics is defined as the analysis of lipids in a given system, their molecular functions, and their interacting molecules(Kishimoto et al 2001, Loizides-Mangold 2013).…”
Section: Introductionmentioning
confidence: 99%